Eksistensi Sektor Pertanian dalam Struktur Perekonomian Kabupaten Bangli - DARMAJAYA, I PUTU YOGA; SURYAWARDANI, I GUSTI AYU OKA; AMBARAWATI, I GUSTI AGUNG AYU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.3, No.2, April 2014, 2018)
The Existence of Agricultural Sector in Bangli Regency Economic Structure Contribution of agricultural sector to economy of Bangli Regency has decreased during 2011-2015 with relatively slow growth. This condition indicates that there has been a structural transformation of the economy, therefore it is necessary to analyze the existence of agricultural sector in terms of its current and future role whether it is still a leading sector or will turn into non-leading sectors. This study uses secondary data in the form of Gross Regional Domestic Product (GRDP) by industry of Bangli Regency and Bali Province in 2011-2015. The data were collected by using document study and analyzed by Location Quotient, Dynamic Location Quotient and Total Shift Share method. The results showed that the agricultural sector is the basis sector in Bangli Regency today and in the future. While the sub sectors in agricultural sector that become the basis is seasonal horticultural crops, annual horticulture and other crops, livestock and forestry and logging. Sub sectors in agriculture sector which are predicted to change the role in the future are food crops, annual plantation and fishery that changes role become basis sector were caused by the location factor. While the annual horticulture sub-sector and livestock are changed into non-basis sub-sectors were caused by the economic structure factor.